Activity for the public benefit and good, or a decline in morals? Recent cases of public death penalties in Prussia in the first half of the 19th century - Kubus, Radosław (Requiem, 2025)
In the 18th century, reforms began in the Kingdom of Prussia to soften the hitherto existing criminal law, despite which public death penalties persisted in the country until the mid- 19th century. During this time, people accused of the most serious crimes could be publicly hanged, beheaded, burned or broken with a wheel. The aim of this article is to attempt to answer the question – how the attitude of the Hohenzollern state’s society towards public executions changed over the course of the first half of the 19th century. The conclusion that can be drawn from an analysis of the records of the last public executions is that throughout the first half of the 19th century there was a growing scepticism about public executions, which reached its peak in the late 1830s and early 1840s. This coincided with the development of societies working for the rehabilitation of repeat offenders. Progressive public pressure eventually led to a change in the law and thus the abolition of public executions in 1851.